Enhancing Cognitive Function in Older Adults through Brain Gym: A Community Implementation in Petoran Hamlet, Surakarta - Hesti Janatunnisa; Didik Iman Margatot; Nur Haryani (Al-Hijrah Indonesia, 2025)
Background: The elderly often struggle to accept the changes and setbacks they encounter. The changes that occur are not only physical, but also cognitive, sexual, and social in nature. Decreased brain function can lead to diseases such as delirium, dementia, psychological disorders, and neurological disorders. Nonpharmacological therapy to prevent cognitive decline in the elderly is an intervention that includes Cognitive Rehabilitation Therapy (CRT), one of which is activity therapy, namely, brain exercises. Objective: This study aimed to evaluate the effectiveness of brain gymnastics application on improving cognitive function in the elderly in Petoran RT 01 RW 07 Jebres Village, Jebres District, Surakarta City. Method: This type of research employs a case study approach, utilizing descriptive methods and administering pre-test and post-test MMSE sheets. Results: Based on the application's results, there is an improvement in cognitive function. Conclusion: There are differences in the final results of cognitive function scores before and after participants were given brain gymnastics, with both groups showing an increase.